The hydrodynamic coefficients for an oscillating 2D rectangular box using weakly compressible smoothed particle hydrodynamics (WCSPH) method - Ramli, Muhammad Zahir (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
An implementation of the weakly compressible smoothed particle hydrodynamics (WCSPH) method is demonstrated to determine the hydrodynamics coefficients through radiation problem of an oscillating 2D rectangular box. Three possible modes of motion namely swaying, heaving, and rolling are carried out to establish the influence of oscillating motions in predicting the added mass and damping. Both solid boundary and fluid flow are modelled by WCSPH and validated by the potential flow and experimental results. Discrepancies observed at lower frequencies are further investigated using different particle resolutions, different time steps, and extending the domain with longer runtime to demonstrate the performance of WCSPH. Finally, flow separation and vortices are discussed and compared with experimental results. ******************************************************** Bagi fenomena yang melibatkan radiasi dalam air, segiempat kotak 2D diosilasikan dengan menggunakan simulasi WCSPH untuk memperoleh pekali hidrodinamik. Mod osilasi terbahagi kepada 3 iaitu sway, heave dan roll. Osilasi dengan mengguna pakai kotak akan mempengaruhi pergerakan air dalam menentukan nilai penambahan jisim dan rendaman. Keseluruhan domain air dan sempadan telah dimodelkan dengan menggunakan WCSPH. Semua model tersebut kemudiannya akan dibandingkan melalui keputusan eksperimen dan teori. Jika keputusan melalui kaedah WCSPH ini berbeza, terutama pada frekuensi rendah, penyelidikan lanjut akan dilakukan dengan menggunakan zarah resolusi yang berbeza, langkah masa yang berbeza dan menambah masa domain ujikaji bagi menilai keputusan WCSPH. Akhirnya, kriteria aliran dan kadar pusaran yang terhasil di sekeliling kotak akan dibincang dan dibandingkan bersama keputusan eksperimen.